Ecology of human behavior: contradictions behind the message of environmental crisis - Cifuentes-Ávila, Fabiola; Díaz-Fuentes, Rolando; Osses-Bustingorry, Sonia (Acta Bioethica, 2018)
The article contributes to the discussion about the current understanding of the ecological behavior of the human being from a relation of utilitarian domination of the environment in contrast to its understanding from the ecological perspective, which responds to a natural model that is part of the relations of its functioning in the ecosystem. In this regard, the paradigm of environmental crisis is discussed, in which such behavior is a serious problem of society. From the authors, the problem would be closely linked to the productive and economic system that promotes the artificialization of the human being, creating false needs that through their consumption ensure the sustainability of the economic model. Critical reflection is proposed from education, towards a new understanding of human behavior whose ecological perspective drives new ecosystemic relations, fundamentally based on collaborative relationships.